STUDI KERAGAMAN RAYAP TANAH DENGAN TEKNIK PENGUMPANAN PADA TUMPUKAN JERAMI PADI DAN AMPAS TEBU DI PERUSAHAAN JAMUR PT. ZETA AGRO CORPORATION JAWA TENGAH - Anang Kadarsah (Bioscientiae, 2005)
Subterranean termites is one kind of termites that live in the soil.  This termites build their nest and find their food in the soil and the woods and trees is as a mainly food for their life. Because of their activities, the subterranean termites as a dangerous animals. The aims of study is looking for and found the kind and the diversity of subterranean termites that live under the rice straw and the bagasse .This research is done with cluster random sampling and collected by baiting technique.   Seven kind of subterranean termites from genus Macrotermes, Microtermes, Odontotermes and Capritermes. All of the  species is subterranean termites, except Capritermes are not potential to destroy the woods.